2017
DOI: 10.3847/1538-4357/aa94c9
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared Excess from the West Hot Spot of the Radio Galaxy Pictor A Unveiled by WISE

Abstract: Mid-infrared properties are reported of the west hot spot of the radio galaxy Pictor A with the Wide-field Infrared Survey Explorer (WISE). The mid-infrared counterpart to the hot spot, WISE J051926.26−454554.1, is listed in the AllWISE source catalog. The source was detected in all the four WISE photometric bands. A comparison between the WISE and radio images reinforces the physical association of the WISE source to the hot spot. The WISE flux density of the source was carefully evaluated. A close investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…The above equation, with the expected β ∼ 0.3 characterizing the downstream of the reverse shock (e.g., Meisenheimer et al 1989;Kino, & Takahara 2004), and so Γ ∼ δ ∼ 1, as well as B 100 µG 1 (see Meisenheimer et al 1989Meisenheimer et al , 1997Isobe et al 2017), gives rad 3 pc for keV energies of the observed synchrotron photons. Interestingly, such a small spatial scale would be in rough agreement with the observed variability timescale as well, since the corresponding light-crossing timescale rad /c 10 yr.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The above equation, with the expected β ∼ 0.3 characterizing the downstream of the reverse shock (e.g., Meisenheimer et al 1989;Kino, & Takahara 2004), and so Γ ∼ δ ∼ 1, as well as B 100 µG 1 (see Meisenheimer et al 1989Meisenheimer et al , 1997Isobe et al 2017), gives rad 3 pc for keV energies of the observed synchrotron photons. Interestingly, such a small spatial scale would be in rough agreement with the observed variability timescale as well, since the corresponding light-crossing timescale rad /c 10 yr.…”
Section: Discussionmentioning
confidence: 87%
“…In the context of the former, one may reiterate on the presence of the extended radio/optical filament perpendicular to the jet axis and located several kpc upstream of the termination shock (Perley et al 1997;Thomson et al 1995;Saxton et al 2002), as well as of the high-brightness temperature compact (pc-scale) radio knots within/around the termination shock (Tingay et al 2008). Regarding the latter, one may note the mid-infrared excess over the integrated radio-to-optical continuum of the entire structure (Isobe et al 2017), as well as the intense power-law X-ray emission, for which both the observed flux and the best-fit slope challenge all simple "one-zone" emission scenarios, ascribing the production of the observed keV-energy photons to either synchrotron or inverse-Compton processes (e.g., Wilson et al 2001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The large-scale radio/X-ray jet in Pictor A originates in the galaxy nucleus, and extends up to hundreds of kiloparsecs beyond the host galaxy to the West (Perley et al 1997); the counter-jet is not prominent at radio frequencies, but can be spotted in deep X-ray maps by the Chandra X-ray Observatory . The hotspots located at both sides of the core at the lobes' edges, mark the termination points of the jet (to the West) and of the counter-jet (to the East); the bright Western hotspot is clearly detected and even, in some cases, resolved at radio, infrared, optical, and Xray frequencies (Roeser & Meisenheimer 1987;Thomson et al 1995;Perley et al 1997;Wilson et al 2001;Werner et al 2012;Isobe et al 2017;Thimmappa et al 2020). The radio lobes appear in X-rays as a low-surface brightness cocoon surrounding the large-scale jets (Grandi et al 2003;Migliori et al 2007;Hardcastle et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a new spectral component was identified from the west hot spot of Pictor A in the MIR band (Isobe et al 2017). From a careful analysis of the MIR data obtained with the Wide-field Infrared Survey Explorer (WISE), a significant MIR excess was unveiled over the power-law (PL) like extrapolation of the synchrotron radio spectrum smoothly connecting to the optical one.…”
Section: Introductionmentioning
confidence: 99%